Removal of Arsenic from Ground Water with Shrimp Shell - Rahman, Mohammad Arifur; Hossain, Mohammad Motahar; Samad, Abdus; Alam, A. M. Shafiqul (Dhaka University Journal of Science, 2012)
A single arsenic decontamination system has been developed using shrimp shell for tube well water with arsenic concentration of 120 ?g/L which could be lowered to15?g/L. Arsenic was removed by this system from water by adsorption through fine particles of shrimp shell. Various conditions of adsorption/desorption of arsenic were investigated. Adsorption column method showed the complete removal of As(III) under the following conditions: initial As concentration, 100?g/L, amount of shrimp shell 3.0g, particle size <355?m, treatment flow rate 0.5mL/min and pH 6.5. Desorption efficiency was found in the range of 81-83% with 4M of NaOH after the treatment of groundwater. A combination of techniques was used to remove nine metals of groundwater. Other inorganic constituents of health concern (Cu, Cd, Mn and Fe) in treated water were below their respective WHO guideline for drinking water. DOI: http://dx.doi.org/10.3329/dujs.v60i2.11489 Dhaka Univ. J. Sci. 60(2): 175-180, 2012 (July)